FOSTERING ENVIRONMENTAL STEWARDSHIP: THE IMPLEMENTATION OF 3R (REDUCE, REUSE, RECYCLE) AT SDN 02 AMPELDENTO - Nisa', Hamidatun; Mutia, Tuti (GEOGRAPHY : Jurnal Kajian, Penelitian dan Pengembangan Pendidikan, 2024)
A caring attitude towards the environment is one of the factors that influence its quality. The environmental conditions at SDN 02 Ampeldento showed that it was not clean, a buildup of plastic waste was found in the school environment. There is a strategy to overcome this problem by cultivating environmental awareness by implementing 3R waste management. This research aims to determine the implementation of 3R waste management at SDN 02 Ampeldento and determine students' environmental care attitudes after implementing 3R waste management. This study uses a qualitative method. Data analysis uses the Miles and Huberman method which consists of three steps, namely (1) data reduction, (2) data presentation, (3) drawing conclusions/verification. The research results show that the implementation of 3R waste management goes through 2 stages, namely socialization by delivering 3R waste management material and implementation through carrying out activities by applying the principles of 3R waste management. The implementation of 3R waste management has succeeded in educating students to care more about the environment.